Salvator Rosa in French literature : from the bizarre to the sublime - Patty, James S. (Studies in Romance languages (Lexington, Ky.), 2005)
"Salvator Rosa (1615-1673) was a colorful and controversial Italian painter, talented musician, a notable comic actor, a prolific correspondent, and a successful satirist and poet. His paintings, especially his rugged landscapes and their evocation of the sublime, appealed to Romantic writers, and his work was highly influential on several generations of European writers. James S. Patty analyzes Rosa's tremendous influence on French writers, chiefly those of the nineteenth century, such as Stendhal, Honoré de Balzac, Victor Hugo, George Sand, and Théophile Gautier. Arranged in chronological o